PERKEMBANGAN SYARAT MENGGADAI TANAH HARTA PUSAKA TINGGI DALAM MASYARAKAT ADAT MINANGKABAU DI KABUPATEN AGAM NAGARI KAMANG MUDIAK - KIKKY FEBRIASI (PREMISE LAW JURNAL, 2015)
In Minangkabau community, tanah pusaka tinggi (adat heirloom land) is prohibited to be sold or mortgaged. Mortgaging an adat heirloom land must fulfill four requirements: ‘mayek tabujua di tangah rumah’ (a corpse stretches out in the living room), ‘rumah gadang katirisan’ (Family house is leaking), ‘gadih gadang alun balaki’ (a spinster), and ‘mambangkik batang tarandam’ (striving for success). The impact of the development of the requirements for mortgaging adat heirloom lands in Agam Nagari Kamang Mudiak District has decreased since there are many of them have been mortgaged by the community. The research used judicial sociological method with descriptive analytic approach. The implementation of mortgaging adat heirloom lands in Nagari Kamang Mudiak always goes along, and its status is still there although today the National law (Article 7 of Law No. 56/Prp/1960) is in effect.  However, this National law is not used by the people in Nagari Kamang Mudiak; they only use their own adat (customary) law.   Keywords: Mortgage Condition, Land Belongs to the Property of High Heritage